ÇARLIK RUSYA DÖNEMİNDE KIRGIZİSTAN'DAKİ EĞİTİM KURUMLARI VE DURUMU - AKIMJAN KYZY, Bukatcha (Scientific Journal of Faculty of Theology, 2015)
Knowing a country‘s history of education has a great importance to shape the future of this country. Today, as it is done in every field in Kyrgyzstan, the problems of education are also discussed with its variaty of aspects, and the issues such as which values should be given priority and the position of national and cultural values in the education policy are discussed. Nevertheless, history of the education system in Kyrgyzstan, the phases it went through, and history of the educational institutions can be ignored. Being able to examine the origins of the education problems in Kyrgyzstan of the present day, to approach to the concept of education comprehensively and to create solutions for these problems requires knowing the history of our educational institutions. In this sense, it is important to analyze a variety of educational institutions, operating in Kyrgyzstan in the past, and their situations due to the aforementioned reasons.